SHARIA FINTECH GROWTH IN INDUSTRY REVOLUTION 5.0 – ALAMI SHARIA STUDY CASE - Awaliyah Alifi; Wahyu Dwi Agung (El-Arbah: Jurnal Ekonomi, Bisnis Dan Perbankan Syariah, 2023)
Currently, the development of fintech (financial technology) is growing in Indonesia, not to mention the syariah economic industry is also competing in financial technology and providing financial services based on Islamic law. A number of studies have shown the potential of sharia fintech applications, along with the future challenges that will be face by syariah fintech in Indonesia. ALAMI Sharia is one of the pioneers in the field of syariah fintech with the specification of crowdfunding funds from the public and channeling it to encourage the development of MSMEs that have difficulty getting capital injections from banks. The growth of ALAMI Sharia which has drastically increased in just 3 years is an interesting case study to discuss that it can become learning material for other syariah fintech. Operational cost efficiency, Strict funding assessment standards, employees dominated by young generations, conducive office-culture, and human resource management that not only emphasizes target achievement but alignment of productivity with Islamic values that are consistently applied have proven to be able to turn ALAMI Sharia into the best syariah fintech in Indonesia today.